2019
DOI: 10.1038/s41588-019-0502-z
|View full text |Cite
|
Sign up to set email alerts
|

Germline NPM1 mutations lead to altered rRNA 2′-O-methylation and cause dyskeratosis congenita

Abstract: designed and performed biochemical and translation-related experiments and analyzed data; D.N. generated the NPM D180del mouse model, designed and executed the experiments; S.G. generated the Npm1 conditional KO mouse model; K.I., S.G. and S.P. performed conditional Npm1 KO experiments; A.H.B., A.M., and R.B.D. designed and performed the HITS-CLIP experiments; D.B. and E.M. performed computational analysis of the HITS-CLIP data; Y.Z. designed and performed the Northern blot experiments; A.C.B. provided critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 77 publications
0
88
0
Order By: Relevance
“…A landmark paper recently and convincingly established that NPM1 is a key mediator of rRNA post-transcriptional modifications in mouse embryonic fibroblasts (MEFs) and HSCs [95]. Nachmani and colleagues [95] demonstrated that NPM1 is associated with a large number of box H/ACA and box C/D snoRNAs, and that the 2'O-Me levels of five 28S rRNA sites are specifically and significantly impaired in Npm1 −/− MEFs, yet no changes in Ψ were detected. NPM1 directly interacts with FBL to promote the correct assembly of box C/D snoRNAs into snoRNPs.…”
Section: Regulation Of Rrna Modificationsmentioning
confidence: 99%
“…A landmark paper recently and convincingly established that NPM1 is a key mediator of rRNA post-transcriptional modifications in mouse embryonic fibroblasts (MEFs) and HSCs [95]. Nachmani and colleagues [95] demonstrated that NPM1 is associated with a large number of box H/ACA and box C/D snoRNAs, and that the 2'O-Me levels of five 28S rRNA sites are specifically and significantly impaired in Npm1 −/− MEFs, yet no changes in Ψ were detected. NPM1 directly interacts with FBL to promote the correct assembly of box C/D snoRNAs into snoRNPs.…”
Section: Regulation Of Rrna Modificationsmentioning
confidence: 99%
“…This is in line with the unexpected 2′-O-methylation alteration observed in X-DC. Very recently, a study linked the rRNA 2′-O-methylation alteration caused by NPM1 mutations to the development of congenital dyskeratosis [116]. These results demonstrate the complex etiology of such diseases and how a common phenotype can arise as the result of different alterations.…”
Section: Discussionmentioning
confidence: 90%
“…Zhou et al, 2017). For instance, germline NPM1 mutations impair the binding capacity of FBL to snoRNAs, which alters rRNA 2 0 -O-methylation and causes dyskeratosis congenita (Nachmani et al, 2019). The internal 2 0 -O-methylation in snRNAs appears to be guided by scaRNAs and is essential for small nuclear RNP (snRNP) formation and splicing in mammals (Izumikawa et al, 2019;Meier, 2017;Yu, Shu, & Steitz, 1998).…”
Section: Snorna Guide-based Rna-protein Interactionsmentioning
confidence: 99%